Pengembangan Sistem Informasi Pendukung Pembelajaran TOEFL Berbasis Knowledge Management - Dwi Rosa Indah; Mgs. Afriyan Firdaus; Andhika Setiadi (Annual Research Seminar (ARS), 2015)
This study emphasizes on development of information systems that can help students in learning TOEFL using Knowledge Management (KM) in case study location, namely the Language Institute of Sriwijaya University based on the results of system analysis and design from previous paper. Information systems development to support Toefl learning have been successfully carried out by adapting the 10-step knowledge management roadmap especially on the third phase that includes the stages of knowledge management interface and knowledge management testing and implementation Results of development of information systems in the form of a draft user interface and display the results of KM system includes three entities a team of experts, lecturers and learners interact with the system in the form of personal page panel user, the management of knowledge, inputting of new knowledge, discovery of knowledge and the problem solving management.